The Role of Natural Resources in Fundamental Tax Reform in the Russian Federation - Bosquet, Benoit (World Bank, Washington, D.C., 2013)
The Russian Federation has one of the richest natural resource endowments in the world. Despite their importance in the Russian economy, natural resources do not contribute as much as they could to public revenues. Large resource rents (excess payments, or above-normal profits generated by natural resources in scarce supply) are dissipated through subsidies and wastage, or appropriated by private interests. Failure to tax this rent means that taxes must be levied elsewhere (on capital and labor) to sustain revenues, thereby depressing investment and employment, or that potential revenues are foregone. Failure to reinvest rent means that Russia perpetuates the tradition of exporting low value-added raw materials and excessive capital outflows, and retards its transition to sustainable economic development. The author provides estimates of the average and total current rent on crude oil, natural gas, and round wood in Russia. The sum of appropriated rent on oil and gas was estimated at US$9 billion in 1999 (in excess of $15 billion in 2000), or about 18 percent of consolidated tax revenues. The appropriated rent on round wood was estimated at US$191-1,032 million. A more appropriate natural resource taxation system would enhance the fiscal role of natural resources as well as create better incentives for resource conservation and environmental protection. Two conditions further reinforce the appeal of such a reform. First, the state still owns most of the natural resources, which theoretically facilitates change in resource pricing and taxation. Second, the cost of adjusting the tax system is relatively low at this time since Russian tax policy is undergoing thorough reform. Increasing rent taxation should be relatively straightforward since the system already exists. What mainly needs to be done is to differentiate the fees to reflect objective rent-generating conditions by withdrawing the rent and imposing higher taxes on profitable resource deposits. A seemingly desirable instrument-true differentiation of rental payments-does not exist in Russia despite legislative provisions that it should. Several natural resource taxes are specific taxes (set per volume), regardless of the market price or production cost. Such taxes favor profitable deposits and penalize marginal ones. The author's study should be given serious consideration in the renewed debate on tax reform and in the context of Russia's structural reform program. It is in line with the proposals of the new governmental economic strategy, particularly with boosting the share of natural resources in generating revenue and reducing income tax rates. The extra advantage to rent taxation and revenue recycling is that it would allow the government to lower the tax burden without leading to a budget deficit.